Penggunaan karet alam untuk pembuatan rubber cots mesin ring spinning - ., Luftinor (Jurnal Dinamika Penelitian Industri, 2015)
The purpose of the research was to get the correct rubber compound formula in the making of Rubber cots for Ring spinning machine. The research was conducted by varying the combination of natural rubber (RSS) and synthetic rubber (NBR) in three level with 100 phr, 75 phr, and 50 phr as well as 70 phr, 60 phr, and 50 phr of Zeosil filler. From the conducted research was obtained nine kinds of rubber compound. All the nine kinds of rubber compound then vulcanized to obtain Rubber cots products, after that physical tests such as hardness test, tensile strength test, tensile stress test, elongation at break test, tear resistance test, abrasion resistance test, density test, compression set test, ozone resistance test and yarn unevenness test. Almost all the results of the physical tests to the Rubber cots compound meet the quality standard, except for the result of hardness test and the tensile test. Optimal condition where the quality standards would be met for the physical test and yarn unevenness test is at the use of RSS 100 phr with 70 phr Zeosil of compound rubber raw material. From that condition was obtained 89 Shore A of hardness, tensile strength of 138 kg/cm2; tensile stress of 130 kg/cm3; elongation at break of 400%, tear resistance of 133 kg/cm3, abrasion resistance of DIN 268 mm3, density of 1.17; permanent compression of 75%; ozone resistance unbroken; and yarn unevenness value is at 13.5U%.Keywords : yarn, spinning, rubber cots, zeosilAbstrakTujuan penelitian adalah untuk mendapatkan formula kompon karet yang tepat dalam pembuatan Rubber cots mesin Ring spinning, telah dilakukan penelitian dengan memvariasikan jumlah karet alam RSS dan karet sintetis (NBR) dalam 3 tingkatan perlakuan masing-masing 100 phr, 75 phr, dan 50 phr serta bahan pengisi Zeosil 70 phr, 60 phr dan 50 phr, diperoleh 9 macam kompon karet. Kesembilan macam kompon karet tersebut divulkanisasi untuk mendapatkan produk Rubber cots, selanjutnya dilakukan uji fisika berupa kekerasan, tegangan putus, tegangan tarik, perpanjangan putus, ketahanan sobek, ketahanan kikis, berat jenis, pampatan tetap, ketahanan ozon dan ketidakrataan benang. Hasil uji sifat fisika karet kompon Rubber cots secara keseluruhan hampir memenuhi standard mutu, kecuali hasil uji kekerasan dan tegangan tarik. Kondisi optimal dimana hasil uji sifat fisika Rubber cots dan uji ketidakrataan benang mendekati standard mutu diperoleh pada kompon Rubber cots I menggunakan bahan baku karet RSS 100 phr dan bahan pengisi Zeosil 70 phr, diperoleh nilai kekerasan 89 shore A, tegangan putus 138 kg/cm2; tegangan tarik 130 kg/cm2; perpanjangan putus 400%; ketahanan sobek 133 kg/cm2; ketahanan kikis 268 DIN mm3; berat jenis 1,17; pampatan tetap 75%; dan ketahanan ozon tidak retak, kemudian diperoleh ketidakrataan benang dengan nilai 13,5U%.Kata kunci : benang, pemintalan, rubber cots, zeosil